2021
DOI: 10.11622/smedj.2020067
|View full text |Cite
|
Sign up to set email alerts
|

Doctors and social media: knowledge gaps and unsafe practices

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Several studies demonstrated a “generation gap” in SM use, where students are more likely than faculty to use SM [ 114 , 115 , 117 , 118 ]. A linear relationship between increasing age and decreasing SM use was also found among physicians of the same specialty or other HCPs [ 85 , 91 , 94 , 95 , 100 , 106 ].…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Several studies demonstrated a “generation gap” in SM use, where students are more likely than faculty to use SM [ 114 , 115 , 117 , 118 ]. A linear relationship between increasing age and decreasing SM use was also found among physicians of the same specialty or other HCPs [ 85 , 91 , 94 , 95 , 100 , 106 ].…”
Section: Resultsmentioning
confidence: 89%
“…Among 88 studies, 49 were quantitative [ 32 , 33 , 35 , 38 - 43 , 51 - 53 , 55 , 59 - 61 , 64 , 66 - 69 , 71 , 72 , 74 , 75 , 77 - 80 , 82 , 85 , 88 , 89 , 91 , 94 - 96 , 98 , 100 , 102 , 105 - 108 , 110 , 113 , 114 , 116 , 118 ], 12 were qualitative [ 34 , 36 , 44 , 45 , 49 , 57 , 73 , 76 , 92 , 93 , 101 , 104 ], and 27 used mixed methods [ 35 , 37 , 46 - 48 , 50 , 54 , 56 , 58 , 62 , 63 , 65 , 70 , 81 , 83 , 84 , 86 , 87 , 90 , 97 , 99 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations